Challenges and Opportunities for Respiratory Syncytial Virus Vaccines - Anderson, Larry J.; Graham, Barney S. (Current Topics in Microbiology and Immunology, 2013)
Although respiratory syncytial virus (RSV) has been a high priority for vaccine development for over 50 years now, still no vaccine is available and none has yet demonstrated sufficient promise to move to licensure. The success of RSV immune prophylaxis and the availability of ever more powerful tools to study the immune response and pathogenesis of disease, combined with the ability to construct a wide variety of vaccines using different vaccine platforms, give us grounds to believe that an RSV vaccine is within reach. This book brings together in one source what is currently known about the virus: its clinical and epidemiologic features; the host response and pathogenesis of the disease; vaccines, vaccine platforms, and treatment; and animal and tissue culture models of RSV infection. It is designed to organize the critical information relevant to RSV vaccine development, facilitate the assimilation of data, and speed progress toward producing a safe and effective vaccine.